Climates of urbanization: local experiences of water security, conflict and cooperation in peri-urban South-Asia. (22nd July 2019) - Roth, Dik; Khan, Muhammad Shah Alam; Jahan, Israt; Rahman, Rezaur; Narain, Vishal; Singh, Aditya Kumar; Priya, Monica; Sen, Sucharita; Shrestha, Anushiya; Yakami, Saroj
ABSTRACT: This article explores changing water (in)securities in a context of urbanization and climate change in the peri-urban spaces of four South-Asian cities: Khulna (Bangladesh), Gurugram and Hyderabad (India), and Kathmandu (Nepal). As awareness of water challenges like intensifying use, deteriorating quality and climate change is growing, water security gets more scientific and policy attention. However, in peri-urban areas, the dynamic zones between the urban and the rural, it remains under-researched, despite the specific characteristics of these spaces: intensifying flows of goods, resources, people, and technologies; diversifying uses of, and growing pressures on land and water; and complex and often contradictory governance and jurisdictional institutions. This article analyses local experiences of water (in-)security, conflict and cooperation in relation to existing policies. It uses insights from the analysis of the case studies as a point of departure for a critical reflection on whether a 'community resilience' discourse contributes to better understanding these cases of water insecurity and conflict, and to better policy solutions. The authors argue that a community resilience focus risks neglecting important insights about how peri-urban water insecurity problems are experienced by peri-urban populations and produced or reproduced in specific socio-economic, political and policy contexts. Unless supported by in-depth hydro-social research, such a focus may depoliticize basically political questions of water (re) allocation, prioritization, and access for marginalized groups. Therefore, the authors plead for more critical awareness among researchers and policy-makers of the consequences of using a 'community resilience' discourse for making sense of peri-urban water (in-)security. Key policy insights There is an urgent need for more (critical) policy and scientific attention to peri-urban water insecurity, conflict, and climate change. Although a changing climate will likely play a role, more attention is needed to how water insecurities and vulnerabilities in South Asia are socially produced. Researchers and policy-makers should avoid using depoliticized (community) resilience approaches for basically socio-political problems.